Characterization of the chloroplast genome of Perilla frutescens (Lamiaceae), an herb plant from China. Issue 2 (2nd April 2020) - Lang, Yuying; Zhang, Zhiwen; Jiang, Jiyue; Cao, Tianyi; Tian, Jun
Abstract: Perilla frutescens is well known for its high α-linolenic acid (ALA) accumulation and medicinal values in the world. In this study, the complete chloroplast genome of P. frutescens was reported. The chloroplast genome length of P. frutescens was 152, 602 bp, which was circular in shape with a characteristic quadripartite structure. It contained a large single-copy (LSC) region of 83, 706 bp, a small single-copy (SSC) region of 17, 546 bp and separated by two inverted repeat (IR) regions of 25, 675 bp. The overall nucleotide content of the chloroplast genome was 38.1% G + C content. This chloroplast genome contained 139 genes, which included 94 protein-coding genes (PCGs), 37 transfer RNA (tRNAs), and 8 ribosome RNA (rRNAs). Phylogenetic and evolutionary relationship have shown that P. frutescens was closely related to P. setoyensis in the family Lamiaceae using the maximum-likelihood (ML) method.